Perencanaan Pour and Flush Toilet di Kampung Cikoneng Babakan Desa Cibiru Wetan Kabupaten Bandung - Dzakiyyah Afifah Aurora; Muhamad Fahmi Farrij; Nissa Syakira Putri W.; Jeremy S. Zebua; Mila Dirgawati; Annisa Ulfa Zakiyyah (Jurnal Serambi Engineering, 2024)
The problem of open defecation (BABS) and the lack of proper toilet infrastructure for the residents of Cikoneng Village, RT 2, Bandung Regency can have a negative impact, especially on the health aspect. The economic situation and lack of public awareness of cleanliness are factors that lead to many latrines being covered only by tarpaulins with bamboo/wooden walls. The communal latrines previously available in Cikoneng village were even less effective due to their non-strategic location and water quantity problems. The purpose of this research is to plan the construction of a Pour and Flush Toilet (PFT) in RT 02 by conducting observations, questionnaires and analysis of technical and non-technical aspects to achieve good sanitation. The results of the research show that 100% of the residents of Kampung Cikoneng RT 2 are aware of the importance of PFT and are willing to participate in the construction, which consists of 4 toilet units and a septic tank with a length of 8.5 m, width of 9 m and depth/height of 8.5 m.